Self-Management Behaviors among Adults with Hypertension in Coastal Communities: A Descriptive Observational Study - Ayuk Cucuk Iskandar; Farhah Kamilah (Faculty of Nursing, Universitas Pelita Harapan, 2026)
Hypertension is a major factor in premature mortality and often goes undetected until complications arise, highlighting the necessity for effective prevention and management strategies. Coastal adults who actively manage their hypertension can improve their health and well-being while reducing the possibility of complications. This study aimed to describe the self-management behaviour of adult hypertensive patients living in coastal areas. A cross-sectional descriptive approach was used. A total of 287 adult patients with hypertension were included as samples in this study based on the established inclusion criteria. This study used the Hypertension Self-Management Behaviour Questionnaire (HSMBQ), which contains 40 questions in the Indonesian language version. The majority of self-management behaviours among adult hypertensive patients were categorised as moderate (67.6%), followed by low (18.5%) and high (13.9%). This distribution highlights a significant opportunity for healthcare providers to implement targeted interventions aimed at increasing self-management skills, particularly for those in the low and moderate categories. Interventions designed to enhance awareness and skills in hypertension management can be tailored to the cultural context of coastal communities, thereby improving the proportion of patients classified in the high category. Enhancing these behaviours could lead to improved blood pressure control and overall health outcomes in this population.